Efecto del uso de diferentes niveles de vinagre de manzana sobre los parámetros productivos en pollos de engorde broiler Cobb 500 - Anchundia Mendoza, Karen Paola (2024)
In this study, the effect of different levels of apple cider vinegar on productive parameters in Broiler Cobb 500 broiler chickens was evaluated, with the purpose of determining productive efficiency, analyzing the benefit/cost and comparing these parameters with a standard diet. The methodology used included an experimental design over six weeks, in which four treatments were implemented: a control group without apple cider vinegar and three experimental groups with 2 ml, 4 ml, and 6 ml of vinegar per liter of water, respectively. During the experiment, feed consumption, body weight, feed conversion and cost-benefit ratio were measured.The group with 6 ml of vinegar per liter (T3) presented the highest feed consumption and weight gain, although the differences were not statistically significant compared to the other treatments. Feed conversion was more efficient in the T3 treatment, especially in the last week of the study. However, cost-benefit analysis indicated that treatment with 2 ml of vinegar per litre (T1) was the most cost-effective, although T3 showed improvements in production parameters.Apple cider vinegar had a positive effect on the production efficiency of broilers, but the differences observed were not significant enough to justify its use on a large scale without a detailed analysis of the balance between cost and benefit.